2018
DOI: 10.1097/cco.0000000000000474
|View full text |Cite
|
Sign up to set email alerts
|

New insights in the pathogenesis of T-cell lymphomas

Abstract: Understanding of PTCL pathogenesis has substantially improved, and oncogenic events have been identified. The current challenge is to mount efficient therapeutic strategies targeting these aberrations to improve patients' outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 80 publications
0
23
0
Order By: Relevance
“…This profile typically consists of epigenetic deregulation (various and often multiple inactivating TET2 +/-DNMT3A mutations, often occurring at early stages in haematopoietic progenitors, present in about 80% and 30-35% of the cases, respectively), 27,28 and second hit mutations with a more restricted distribution. 29 The latter include a hotspot RHOA G17V mutation encoding a dominant negative variant of the protein in up to 70% of cases, and other gain-offunction mutations targeting the TCR signalling pathway (PLCG1, CD28, FYN, PIK3 components, CARD11, etc.). [30][31][32] Mouse models have shown that RHOA G17V induces TFH specification, autoimmunity, and promotes lymphomagenesis in the presence of TET2 inactivation, indicating the synergistic effect of both mutations.…”
Section: Pathological Features Of Nodal-based Ptclsmentioning
confidence: 99%
“…This profile typically consists of epigenetic deregulation (various and often multiple inactivating TET2 +/-DNMT3A mutations, often occurring at early stages in haematopoietic progenitors, present in about 80% and 30-35% of the cases, respectively), 27,28 and second hit mutations with a more restricted distribution. 29 The latter include a hotspot RHOA G17V mutation encoding a dominant negative variant of the protein in up to 70% of cases, and other gain-offunction mutations targeting the TCR signalling pathway (PLCG1, CD28, FYN, PIK3 components, CARD11, etc.). [30][31][32] Mouse models have shown that RHOA G17V induces TFH specification, autoimmunity, and promotes lymphomagenesis in the presence of TET2 inactivation, indicating the synergistic effect of both mutations.…”
Section: Pathological Features Of Nodal-based Ptclsmentioning
confidence: 99%
“…Novel insights gleaned from high-throughput molecular and genomic profiling studies have contributed significantly to the understanding of peripheral T and NK cell lymphomas. The identification of a multistep oncogenic pathway which involves epigenetic deregulation related to TET2, DNMT3, or IDH2 mutations and mutations affecting genes related to TCR signaling pathway in nodal lymphomas of follicular helper T cell origin has been a major advancement [4]. Similarly, the uncovering of unique gene expression profiles with the identification of dysregulated signaling pathways [57], as well as the characterization of the mutational landscape via mutational profiling techniques in ENKTL, is providing new insights into the pathogenesis of this disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…To account for the complex genomic landscape of AITL, a multistep tumorigenesis model was proposed (41)(42)(43). The premalignant hematopoietic progenitor cells harboring mutations (e.g., TET2 and DNMT3A) are predisposed to the development of blood cancer, and the acquisition of second-hit mutations (e.g., RHOA G17V and IDH2 R172 ) in a subclone of TFH cells eventually leads to AITL.…”
Section: Multistep Tumorigenesis Modelmentioning
confidence: 99%